Product sophistication and the slowdown in Chinese export growth - Mark Kruger; Walter Steingress; Sri Thanabalasingam (Bank of Canada, 2017)
Chinese real export growth decelerated considerably during the last decade. This paper argues that the slowdown largely resulted from China moving to a more sophisticated mix of exports: China produced more sophisticated goods over which it had pricing power instead of producing greater volumes of less sophisticated products. Indeed, we show that the share of highly sophisticated products in Chinese exports increased steadily over time and that Chinese exports became less price sensitive, suggesting increased pricing power. Further, a decomposition of China's market share gains shows that China continues to gain market share despite exporting products with higher-than-average world prices. China's continuous gain in global export market share suggests that its export machine is far from broken.
Keywords: F14; F17; O10; 330; International topics; Exchange rates; Development economics